2009
DOI: 10.2217/rme.09.61
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of the Vasculature within the Neural Stem Cell Niche

Abstract: An interdependent relationship between the vascular and nervous systems begins during the earliest stages of development and persists through the mammalian lifespan. Accordingly, the process of adult neurogenesis involves the coordinated response of both systems to maintain a specialized microenvironment (niche) that tips the scale towards maintenance or regeneration, as needed. Understanding the nature and regulation of this balance will provide a foundation on which the potential for molecular-and stem cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 206 publications
3
75
0
1
Order By: Relevance
“…In principle, BVs may impact SC performance not only by virtue of providing perfusion and distributing blood-borne factors but also in a perfusion-independent manner via production of paracrinically acting "angiocrine" factors (47)(48)(49). Could enhanced neurogenesis be due simply to a quantitative increase of the niche vasculature or, alternatively, to some qualitative change associated with vascular "rejuvenation"?…”
Section: Discussionmentioning
confidence: 99%
“…In principle, BVs may impact SC performance not only by virtue of providing perfusion and distributing blood-borne factors but also in a perfusion-independent manner via production of paracrinically acting "angiocrine" factors (47)(48)(49). Could enhanced neurogenesis be due simply to a quantitative increase of the niche vasculature or, alternatively, to some qualitative change associated with vascular "rejuvenation"?…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the SIRT1 action shown here provides a potential explanation for the effect of environmental stimuli on adult hippocampal neurogenesis. Moreover, aNSCs/ aNPCs are distributed near blood vessels in the adult SVZ and SGZ (Goldberg and Hirschi, 2009), and could thus quickly respond to energy changes by sensing the oxygen and nutrient signals from the blood vessels. We showed that SIRT1 could partially mediate the effect of 2-DG-induced metabolic stress on aNSC proliferation in vitro, but the in vivo evidence of SIRT1 involvement in metabolic control of adult neurogenesis remains to be further studied.…”
Section: Metabolic Regulation Of Adult Neurogenesismentioning
confidence: 99%
“…The intermittent absence of astrocytic and PC contact with the vessel allows for transit-amplifying NSCs to directly contact the endothelium, enabling rapid signaling, and molecular exchange between the two cells (Girouard and Iadecola, 2006). The unique SVZ microvasculature suggests that a modified BBB in this niche exists (Goldberg and Hirschi, 2009).…”
Section: Cytoarchitecturementioning
confidence: 99%
“…Type-B cells control capillary tone in the SVZ due to the contractile nature of PCs (Goldberg and Hirschi, 2009). As a result, the interactions between vascular cells and NSCs are critical to the SVZ functioning as a neurogenic network.…”
Section: Cytoarchitecturementioning
confidence: 99%